Напряженно-деформированное состояние составной матрицы штампа при полугорячем выдавливании металлов - Лавинский, Денис Владимирович (НТУ "ХПИ", 2003)
The analysis of thermal loading on strength and stiffness of semi hot extrusion die was considered in this article. The finite element method which is realized as program package SPACE-T was chosen as tool of solution. The contact interference was solved with contact layer method help
Keywords: модуль упругости; теплопроводность; SРАСЕ-Т комплекс; пластические деформации; рабочая вставка